2003
DOI: 10.1007/s00147-003-0614-2
|View full text |Cite
|
Sign up to set email alerts
|

Marginal grafts: finding the correct treatment for fatty livers

Abstract: The influence of steatosis on the outcome of orthotopic liver transplantation (OLT) was evaluated in 860 liver transplantations carried out in 784 patients from October 1990 to August 2001. Donor variables considered were: age, hepatic enzymes, bilirubin, total and warm ischemia times, macrovesicular and microvesicular steatosis. Recipient variables considered were: age, UNOS status, Child-Pugh score and indication for OLT. Patient and graft survival were the main outcome indicators. Macrovesicular steatosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 20 publications
(3 reference statements)
0
33
0
3
Order By: Relevance
“…have shown that even a macrovesicular steatosis of 15% results in an approximately 20% shorter graft and patient survival. This effect was aggravated if the CIT was longer than 10 h, the recipient was hepatitis C virus positive, or the donor age was >65 years .…”
Section: Discussionmentioning
confidence: 99%
“…have shown that even a macrovesicular steatosis of 15% results in an approximately 20% shorter graft and patient survival. This effect was aggravated if the CIT was longer than 10 h, the recipient was hepatitis C virus positive, or the donor age was >65 years .…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Verran et al, 6% of patients receiving grafts with severe macrovesicular fat required retransplantation within 3 months versus 1.4% of those receiving mildly steatotic grafts (Verran et al, 2003). In another multivariate analysis by Salizzoni et al, cumulative adverse factors on the incidence of PGNF included donor age, recipient HCV viremia, and prolonged CIT by use of grafts with over 15% macrovesicular steatosis (Salizzoni et al, 2003).…”
Section: Steatosismentioning
confidence: 99%
“…Within the degree of fat accumulation in the hepatocytes, the histological evaluation of steatosis can be qualified in two major patterns: microvesicular and macrovesicular steatosis. Microvesicular steatosis solely has been shown to have no negative impact on outcome . Yet, several studies have shown that moderate and severe macrovesicular steatosis of liver grafts is associated with impaired graft function after transplantation .…”
Section: Introductionmentioning
confidence: 99%